Faith in freedom : Muslim immigrant women's experiences of domestic violence - Ghafournia, Nafiseh (MUP Islamic studies series, 2019)
How do Australian Muslim immigrant women understand domestic violence? How do they experience domestic violence? How do they respond to domestic violence? What role does their faith play? How do immigration-related factors intersect with culture, religion and gender to shape the women's experiences of domestic violence and responses to it? Faith in Freedom answers the above questions by analysing the Muslim immigrant women's own narratives of domestic violence. The study contributes to understandings of the intersections between factors such as gender, culture, religion and immigration, and the ways in which different social locations interact in Muslim immigrant women's experiences of abuse. Faith in Freedom examines the implications of feminist intersectional perspectives for service provision, social work education and policy.--